On the Integration of Production and Financial Hedging Decisions in Global Markets - DING, Qing (Institutional Knowledge at Singapore Management University, 2007)
We study the integrated operational and financial hedging decisions faced by a global firm who sells to both home and foreign markets. Production occurs either at a single facility located in one of the markets or at two facilities, one in each market. The company has to invest in capacity before the selling season starts when the demand in both markets and the currency exchange rate are uncertain. The currency exchange rate risk can be hedged by delaying allocation of the capacity to specific markets until both the currency and demand uncertainties are resolved and/or by buying financial option contracts on the currency exchange rate when capacity commitment is made. A mean-variance utility function is used to model the firm's risk aversion in decision making. We derive the joint optimal capacity and financial option decision, and analyze the impact of the delayed allocation option and the financial options on capacity commitment and the firm's performance. We show that the firm's financial hedging strategy ties closely to, and can have both quantitative and qualitative impact on, the firm's operational strategy. The use, or lack of use of financial hedges, can go beyond affecting the magnitude of capacity levels by altering global supply chain structural choices, such as the desired location and number of production facilities to be employed to meet global demand. [PUBLICATION ABSTRACT]